A Study on the p Bond of Benzene and Hydrogen Chloride Interaction - Yang, Jie; Li, Shaobo; Yang, Benhong; Shao, Guoquan; Yin, Qiyi (Asian Journal of Chemistry, 2013)
We applied ab initio theoretical studies on the complex of C6H6 and n(HCl), formed by X-H···p bond complexes. First, the monomers and complex were optimized at the MP2/cc-pVTZ level. Then, we regulated the BSSE and calculated the binding energy of different systems at the same level with the correction of BSSE by using counterpoise method at the MP2/aug-cc-p VTZ level. The results demonstrated that C6H6···n HCl (n = 1 to 12), with increasing hydrogen chloride number, the binding energy of complex present in the overall increasing trend, however, the p bond of C6H6···(HCl)n at least interact to 12 hydrogen chloride to formation of X-H···p bond complexes.